2014
DOI: 10.5858/arpa.2013-0388-oa
|View full text |Cite
|
Sign up to set email alerts
|

ALKRearrangement in a Large Series of Consecutive Non–Small Cell Lung Cancers: Comparison Between a New Immunohistochemical Approach and Fluorescence In Situ Hybridization for the Screening of Patients Eligible for Crizotinib Treatment

Abstract: Our results show that IHC may be a useful technique for selecting NSCLC cases to undergo ALK FISH analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 40 publications
3
46
0
1
Order By: Relevance
“…Formalin‐fixed paraffin‐embedded samples were sectioned at a thickness of 4 μm and subjected to immunohistochemical staining with a rabbit monoclonal primary anti‐ALK antibody (clone D5F3) using the OptiView DAB IHC Detection Kit and the OptiView Amplification Kit (Ventana Medical Systems Inc., Tucson, AZ, USA). The entire staining procedure was performed using the fully automated assay using BenchMark XT slide stainer system (Ventana Medical Systems Inc.) . Positive immunostaining for ALK was clearly visible as strong, granular, cytoplasmic staining in tumour cells.…”
Section: Methodsmentioning
confidence: 99%
“…Formalin‐fixed paraffin‐embedded samples were sectioned at a thickness of 4 μm and subjected to immunohistochemical staining with a rabbit monoclonal primary anti‐ALK antibody (clone D5F3) using the OptiView DAB IHC Detection Kit and the OptiView Amplification Kit (Ventana Medical Systems Inc., Tucson, AZ, USA). The entire staining procedure was performed using the fully automated assay using BenchMark XT slide stainer system (Ventana Medical Systems Inc.) . Positive immunostaining for ALK was clearly visible as strong, granular, cytoplasmic staining in tumour cells.…”
Section: Methodsmentioning
confidence: 99%
“…We used Deek's funnel plots of lnDOR against 1/ESS 1/2 , or, equivalently, against (1/ n 1 + 1/ n 2) 1/2 , which is proportional to 1/ESS 1/2 , to assess the accuracy of diagnostic tests [40]. The p value obtained from the funnel plot was 0.001, indicating the presence of publication bias in this meta-analysis (Figure 10).…”
Section: Resultsmentioning
confidence: 99%
“…PCR, another method for detecting ALK fusion, is associated with high false positive rates, limiting its clinical utility. Some researchers have reported that IHC, a cost-effective and simple assay, can be used to screen for ALK rearrangements [40, 54], and three different antibodies are used for this purpose in clinical practice. D5F3, one of these antibodies, is widely used in clinics; we therefore conducted this systematic review and meta-analysis to assess the diagnostic accuracy of D5F3 IHC assays in detecting ALK rearrangement in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Squamous histology has a lower rate of actionable genetic changes than adenocarcinoma of the lung, but epidermal growth factor mutations and anaplastic lymphoma receptor tyrosine kinase rearrangements, for example, have been described in squamous cases, albeit rarely. 3,4 In reality, histology is a subjective determination by a pathologist. Previous reports have suggested very low k-values for agreement between pathologists on whether an NSCLC exhibits squamous histology.…”
Section: Ross Camidgementioning
confidence: 99%